2019
DOI: 10.1002/imhj.21765
|View full text |Cite
|
Sign up to set email alerts
|

Like mother, like child? Maternal determinants of children's early social‐emotional development

Abstract: Social‐Emotional competencies evolve early in life. For example, early emotion regulation is learned primarily in the context of mother–child interaction, which may allow for maternal influences to shape children's social‐emotional development. The aim of the current study was to longitudinally examine maternal determinants of children's early social‐emotional development in a community‐based sample of first‐time mothers (N = 61, aged 22–39 years). Specifically, we used structural equation modeling to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 66 publications
2
34
0
7
Order By: Relevance
“…This pattern of response predicted maternal depressive disorder, which in turn was related to poorer infant development. It has been reported that mothers’ sensitivity is related to bonding and social and emotional behavioral problems ( 53 ). Thus, maternal factors impacting the quality of mother-child interaction are important for children’s positive social-emotional development.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern of response predicted maternal depressive disorder, which in turn was related to poorer infant development. It has been reported that mothers’ sensitivity is related to bonding and social and emotional behavioral problems ( 53 ). Thus, maternal factors impacting the quality of mother-child interaction are important for children’s positive social-emotional development.…”
Section: Discussionmentioning
confidence: 99%
“…Among those symptoms, maternal depression is most studied, since major depression disorder is particularly prevalent in mothers (Kessler, 2003). One study supports this relation by showing that maternal depression is negatively associated with their own sensitive response toward their children's emotion expression (Behrendt et al, 2019). Another study added anxiety in addition to depression and found that both symptoms correlate with lower emotional awareness of their children (Moreira et al, 2019).…”
Section: Psychopathology and Esmentioning
confidence: 99%
“…Parent-to-infant attachment emerges as an important factor contributing to the quality of the subsequent reciprocal relationship, as well as to the well-being and the development of the child (Young, 2013;Parfitt et al, 2014). A stronger parentto-infant attachment promotes the child's social, cognitive, and behavioral development (Schenk et al, 2005;Mason et al, 2011;Ip et al, 2018) as well as better mother-child interactions which in turn improve child's emotional regulation (Klaus and Kennell, 1982;Cigoli et al, 2006;Mason et al, 2011;Behrendt et al, 2018Behrendt et al, , 2019Brake et al, 2020;Ponti et al, 2020). In addition, parents with higher levels of parent-to-infant attachment have higher responsiveness and sensitivity, which promote the development of a child's secure attachment and the infant's exploration of the environment maintaining an appropriate level of stimulation (Ainsworth et al, 1971;Solomon and George, 1996;Siddiqui and Hägglöf, 2000;Sandbrook and Adamson-Macedo, 2004;Blair et al, 2006;Rossen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%